Vibração das pregas vocais em diferentes frequências: análise teórico-experimental - Isadora e Souza Guerci de Oliveira (2017)
Introduction: The vocal folds are known to be protagonists participating in the production of vocal sound having an important role in voice production and speech.The oscillation of the vocal folds, responsible for voice production, is a complex process because it results aspects involving aerodynamics, physiological and biomechanical issues. Due to its importance and complexity, the vocal folds have been the source of many studies involving joint multidisciplinary areas in developing research involving the vocal tract and bioengineering. Objective: The main objective of this thesis is the analysis of the behavior of the vocal folds, using measurements of vocal parameters of volunteers who were used as input data into a mathematical model nonlinear discrete mass-spring for predicting the movements in different vocal frequencies. The IF72 model developed by Flanagan and Ishizaka (1972) was implemented. The simulations were performed for normal, low and high voice frequencies, to understand the different settings in the vocal fold structure in the various emissions. It is hoped that this study can contribute to better understanding of the vibration behavior of the vocal folds and glottal closure. Methodology: four professional singers were recruited to participate in the study as volunteers, two male and two female, aged between 18 and 55 years. The study was performed in two stages: the first corresponded to the analysis of a database containing the record of four voices, two female and two male, issued in each of the three voice frequencies for each evaluation. For each volunteer was held the following process: collecting the material of voice for each participant in the emission frequency and intensity of normal speech, identifying the frequency emitted by the singer, emission in high frequency and low frequency. These emissions were made for acoustical ratings, eletroglotográfica (EGG), aerodynamics and to collect Laryngeal assessment data. The second stage consisted of the implementation of the model proposed by Flanagan and Ishizaka (1972) nonlinear in MATLAB software. For implementation of the two non-linear mass model was created a script complying with the directives and parameter values used in the literature (Ishizaka and Flanagan, 1972). Results: A relationship was found between the fundamental frequency values of the results obtained in the simulation and analysis methods of the vocal folds. There was agreement between the speed quotient of simulation and the high speed laryngoscopy (HSV). For the contact quotient was observed nearby values of the simulation and EGG values. Analyzing glottal area was noted significant differences in maximum glottal area values between the simulation and HSV. Regarding the glottal flow it was observed that this parameter was greatly influenced by values related to subglottic pressure put as input data from the implementation model in MATLAB. Conclusion: The use of mathematical models was useful in studies of the motion characteristics of the vocal folds. However, the difficulty of obtaining actual parameters (measured 'in loco') to be used as input data for simulations what were important sources of variation in the results.